HUBUNGAN KEKUATAN OTOT LENGAN DENGAN BAHU DENGAN KEMAMPUAN SERVICE BAWAH BOLA VOLI MINI PADA SISWA PUTERA KELAS V SDN 015 KECAMATAN SENTAJO RAYA - Juita, Ardiah; ', Fitriani; ', Drs. Ramadi., S.Pd., M.Kes AIFO (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
ABSTRACT, The problem in this research is not maximal yet ability of under service volleyball mini on male student class V SDN 015 Sentajo Raya district. This is presumably due to the low strength of the arm and shoulder muscles. So the author wants to prove the corelation between muscle strength of arms and shoulders with the ability of under service volleyball mini on male student class V SDN 015 Sentajo Raya district. The method used is the correlation method. The sample in this research are male students class V SDN 015 Sentajo Raya District totaling 14 students. The sample selection using total sampling technique. The analysis in this study used correlational. Based on the analysis of data obtained by the value of r count is 0.594 with the value rtabel = 0.532, it means rhitung = 0.594> rtabel = 0.532 and it can be said that there is a corelation between muscle strength of arms and shoulders with the capability of under service volleyball mini game male students class V SDN 015 District of Sentajo Raya. The next test signifikaan, obtained t = 2.56, while ttabel with df = n-2 = 14-2 = 12 at 95% confidence level is 1.782. Ho hypothesis testing criteria accepted if thitung smaller than ttabel while the calculation results show that t = 2.56> table = 1.782, thus the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) that